An interesting new species of Kamimuria (Plecoptera: Perlidae) from China, with notes on K. grandispinata Du & Sun - Li, Weihai; Mo, Raorao; Yang, Juan (Zootaxa, 2019)
Kamimuria circumspina sp. n. from Wuling Mountains in Guizhou Province, China, is described as new to science. The morphological characters of the new species are discussed and compared with similar perlid taxa and congeners. Kamimuria grandispinata Du & Sun is rediscovered from the same mountain range.